Angola : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2007)
This Selected Issues paper and Statistical Appendix on Angola underlie monetary policy framework. Angola has adopted an anti-inflation policy that has led to a sharp decline in inflation. To institute a monetary policy framework, a nominal anchor or constraint on the value of domestic currency must be established. Additional work to fine-tune the measures of currency in circulation, conduct more sophisticated tests to assess the relationship between inflation and the monetary aggregates, and determine how to incorporate the currency measure in monetary operations is needed.